Pengembangan Infrastruktur Sipil Berbasis Lingkungan Pasca Pandemi Covid-19 di Kelurahan Anduonohu Kota Kendari - Welendo, La; Ahmad, Siti Nurjanah; Mursidi, Baso; Nasrul, Nasrul; Nuhun, Ridwan Syah; Putra, Adris A. (Vokasi Universitas Halu Oleo, 2021)
The realization of an increase in the community's economy with access to roads, especially on roads in theAnduonohu Urban Village, Kendari City, which are still limited in the formation of roads, as a form of highereducation tridarma and shared responsibility for the benefit of the community, the purpose of carrying out thisservice is to provide understanding and application of infrastructure development civilian construction ofenvironmental roads during the post-Covid-19 pandemic to facilitate access to community mobility in thatenvironment and so that people can understand the importance of road infrastructure for the sustainability ofthe economy of the surrounding community.The process of implementing this service activity is the application of a technique for making newenvironmental roads and repairing existing footpaths according to the available resources of the communityservice implementing TEAM, namely socialization to the community by paying attention to work patternsduring the Covid-19 pandemic according to standard health protocols set. The road construction implementationtechnique conveyed in this service activity is in the form of increasing public knowledge, especially in theprocedural implementation of civil infrastructure, as well as maintaining the cleanliness and health of theenvironment around their residence.The process of implementing this service activity is the application of atechnique for making new environmental roads and repairing existing footpaths according to the availableresources of the community service implementing TEAM, namely socialization to the community by payingattention to work patterns during the Covid-19 pandemic according to standard health protocols set. The roadconstruction implementation technique conveyed in this service activity is in the form of increasing publicknowledge, especially in the procedural implementation of civil infrastructure, as well as maintaining thecleanliness and health of the environment around their residence. The method used in this activity is sampleprovide, direct and face-to-face discussions with the community, as well as field applications in the developmentof civil infrastructure in Anduonohu Village, Kendari City. The results obtained by this community serviceprogram are that the community can understand the importance of science and the manufacture ofenvironmental road physical infrastructure, the community has a fairly good response and high enthusiasm forthe implementation of this program of activities, it can benefit the community by forming environmental roadswith more pavement. both for the movement / mobility of the community in that location and the locationaround it. Keywords: Civil Infrastructure, Environmental Road, Community, Covid-19 Pandemic